Research and Dynamic Analysis of a Cable Reel Device Based on Constant Tension - Li, Hengcan (Manufacturing Technology Journal, 2024)
A constant tension cable reel based on planetary gear transmission is introduced. The parameters of the mechanism are determined to analyze the speed and torque of the transfer mechanism. The relationship between the thread pitch and cable type show that different cable models require different parameters for the constant tension cable reel. The mechanism is designed to automatically adjust the force required for cable pulling and maintain a constant maximum tension. Then the relationship between the moment and speed of each output shaft is analyzed, and the operation mode of the cable reel was explained. The experimental results show that the proposed cable reel can pull the cable flexibly while providing the required constant tension, without damaging the cable and extending its service life. The pitch of the screw-thread pair is directly related to the required tension of the cable and the cable diameter. If the power supply cable model is different, the parameters of constant tension cable reel are also different.
Keywords: Cable reel; Planetary gear; Friction disk; Constant tension; Flexible cable pulling